Cotton Cost-Return Budget in Central Kansas - Warmann, Gerald W.; Miller, Kent B. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on production of cotton in central Kansas.
MF939_1995_10
Keywords: MF939; Economics; Crops; MF